HUMAN TRAFFICKING DALAM PANDANGAN HUKUM ISLAM ATAS PRAKTEK PERBUDAKAN ZAMAN ROSULULLAH - Miftahol Fajar Sodik (Indonesian Journal of Law and Islamic Law (IJLIL), 2020)
Human trafficking is a form of the early occurrence of slavery on earth, it happened long before the arrival of Islamic teachings even though the religion of that religion succeeded in erasing such civilization towards dignified human values. The arrival of Islamic religious teachings at first seemed to support human trafficking with the primary fact that the Prophet Muhammad and his followers were involved in slave ownership obtained from conquest as a result of a war, but this is an argument that departs from the negative analysis of the haters of Islam so that if the teachings of this religion are studied in a concrete way it will be revealed that Islam is trying to change a civilization in a very solution. Keywords: ,,